PERAN PEMERINTAH DAERAH PROVINSI RIAU DALAM PENGELOLAAN DAERAH ALIRAN SUNGAI SIAK: STUDI KASUS DAERAH HILIR DAERAH ALIRAN SUNGAI SIAK TAHUN 2010-2013 - Lestari, Reski; Ridwan, Muhammad (Universitas Riau, 2014)
This reseacrh is aimed to figure out how is the role of Riau Province Local Governmenton Siak Watershed Management (known as Daerah Aliran Sungai, DAS). It is focused to thedownstream watershed of Siak River area which located in Palas Village (Kampar Regency)-Pekanbaru City- Perawang Town (Siak Regency)- Siak Sri Indrapura Town and comes down inTanjung Belit Village (Apit river, Siak Regency), considering to the most complex problem existson it. Those problems consist of domestic waste, industry waste, residential issue. The mainobjective of this research is how the role of Riau ProvinceLocal Government on DASmanagement and learn what the factors influnce it. The research is aimed to analyze the role ofLocal Government in the Province of Riau on DAS management.The type of this reseacrh is description, which means the researcher gives a descriptionor illustration about related phenomenon or social symptom which is analyzed by describingindependent variable systematicly and accurately. Data collection method is done by IndepthInterview, partisipative observation and documnetation study. The result of analysis shows thatthe role of local government on DAS management of downstream is based on Main Duty andFuctionof each Departement. Department of Planning Development Region (knowns as BadanPerencanaan Pembangunan Daerah, Bappeda) Riau Province has a role on planningdevelopment, Departement of Living Environment (known as Badan Lingkungan Hidup, BLH)has a role on managing industry and domestic waste, Departement of Public Project (known asDinas Pekerja Umum, PU) Riau Province Resicence Division has a role on residentmanagement. A department of Local Doverment and others is low coordination and cooperationon management implementation, while cooperation of each department is needed on DASmanagement.Keywords: Role,Coordination, River Stream District